PENERAPAN METODE MODULUS FUNCTION (MF) UNTUK PENYISIPAN PESAN PADA CITRA DIGITAL - Raimah Handayani Harahap; Nelly Astuti Hasibuan; Imam Saputra (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2019)
Steganography is the science and art of hiding (embedded) information by inserting secret messages in other messages. Steganography in the field of information technology is highly developed, namely for digital devices. Information or messages that can be hidden varies, as can messages that are embedded objects. Variations of messages that are normally subject to insertion objects are text messages, picture messages, audio messages, and video messages. The steganography method used is the Modulus Function (MF) method. This method can insert more messages into pixels that have high contrast values. The research conducted is applying the Modulus Function (MF) method for inserting messages into image files. Based on the test results, it can be concluded that by using the Modulus Function (MF) method, the capacity of the image to insert a message is smaller than the image size, the processing time in this method is quite fast, the image quality after inserting a message has good quality, but this method is also still good. has disadvantages, because it is not resistant to manipulation and in some images are still detected by the matlab application.Keywords: Steganography, Implementation, Modulus Function (MF), Image file.